2007
DOI: 10.1126/science.1144124
|View full text |Cite
|
Sign up to set email alerts
|

Toward Direct Measurement of Atmospheric Nucleation

Abstract: Atmospheric aerosol formation is known to occur almost all over the world, and the importance of these particles to climate and air quality has been recognized. Although almost all of the processes driving aerosol formation take place below a particle diameter of 3 nanometers, observations cover only larger particles. We introduce an instrumental setup to measure atmospheric concentrations of both neutral and charged nanometer-sized clusters. By applying the instruments in the field, we come to three important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
489
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 508 publications
(523 citation statements)
references
References 25 publications
31
489
2
1
Order By: Relevance
“…Ambient measurements and modeling studies suggest that nucleated particles can grow into the size range of cloud condensation nuclei (CCN) in various environments ranging from remote continental to highly polluted [Kerminen et al, 2005;Laaksonen et al, 2005;Pirjola et al, 2002;Wang and Penner, 2009;Kuang et al, 2009;Wiedensohler et al, 2009]. Recently, it has been proposed that nucleation of new particles happens by activation of thermodynamically stable clusters that are either charged [Horrak et al, 1998;Kulmala et al, 2000;Yu and Turco, 2008] or neutral [Kulmala et al, 2007], and continually present in the atmosphere. Many proposed nucleation mechanisms involve sulfuric acid and other highly soluble species [Curtius, 2006;Kuang et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Ambient measurements and modeling studies suggest that nucleated particles can grow into the size range of cloud condensation nuclei (CCN) in various environments ranging from remote continental to highly polluted [Kerminen et al, 2005;Laaksonen et al, 2005;Pirjola et al, 2002;Wang and Penner, 2009;Kuang et al, 2009;Wiedensohler et al, 2009]. Recently, it has been proposed that nucleation of new particles happens by activation of thermodynamically stable clusters that are either charged [Horrak et al, 1998;Kulmala et al, 2000;Yu and Turco, 2008] or neutral [Kulmala et al, 2007], and continually present in the atmosphere. Many proposed nucleation mechanisms involve sulfuric acid and other highly soluble species [Curtius, 2006;Kuang et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Recent instrumental development has brought aerosol measurements down to the size of individual molecules and molecular clusters (Gamero-Castoño & Fernandez de la Mora 2000; Kulmala et al 2007b;Mirme et al 2007;Sipilä et al 2008;Winkler et al 2008a;Jiang et al 2011;Vanhanen et al 2011). Instruments that can detect even the smallest particles are needed for studying atmospheric nucleation (Kerminen et al 2010), and they can have various applications also in the fields of nanotechnology, medicine, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we term such aerosols delayed primary aerosols, because particle precursors exist already in the undiluted exhaust and the amounts and characteristics of the resulting atmospheric particulate matter do not depend significantly on atmospheric processing or atmospheric photochemistry. In the secondary aerosol formation process driven by atmospheric photochemistry, volatile gaseous compounds emitted by traffic are chemically transformed in the atmosphere to less volatile species, enabling and enhancing secondary aerosol particle formation via condensation, as well as new particle formation (20-22) Whereas the primary and delayed primary particle emissions affect mostly the air quality near the emission source, the effects of the secondary processes are more important on a regional scale.Previous research has demonstrated the importance of nanosized clusters in atmospheric processes, especially in the formation of ultrafine particles (23,24). Some studies have also shown that nanosized clusters have a role in engine emission formation (4, 25).…”
mentioning
confidence: 99%
“…Previous research has demonstrated the importance of nanosized clusters in atmospheric processes, especially in the formation of ultrafine particles (23,24). Some studies have also shown that nanosized clusters have a role in engine emission formation (4, 25).…”
mentioning
confidence: 99%